Evaluation of the Effects SK-P-9701 (Dextranomer paste) for the Treatment of Various Skin Ulcers - Kawai, Shuzo; Suzuki, Kenji; Nishijima, Setsuko; Izeki, Hiromi; Soh, Hiroshi; Horio, Takeshi; Kondo, Masako; Kondo, Setsuko; Koumura, Jinro; Moriguchi, Takahiko; Inagawa, Kiichi (Skin research, 2000)
SK-P-9701 (Dextranomer paste) was given to 30 patients with various kinds of skin ulcers (decubitus, burn ulcer, leg ulcer, post-operation ulcer and the other ulcers) for 4 weeks to examine the efficacy, safety, usefulness and usability. In the efficacy evaluation, 13 patients revealed “markedly effective”(54.2%), and 8 patients showed “effective”(33.3%), so that the effective rate was 87.5%. In the safety evaluation, SK-P-9701 was “safe”for the treatment of ulcers without any adverse reactions in 22 patients (88.0%). Two patients complained of pain in ulcers after topical application of the test material. Taken together, the usefulness evaluation was “markedly useful” in 9 patients (42.9%), and “useful” in 8 patients (38.1%), so that the useful rate was 81.0%(17/21). The usability of the paste on the ulcer surface was evaluated as “good” in 28 cases (93.3%). As a result, these findings indicate the efficacy and safety of SK-P-9701 in the management of various skin ulcers.